PENENTUAN BENTUK USAHA SYARIAH – PT. BANK DANAMON, TAHUN 2011 – 2014 - Imam Haryanto (Research Center and Case Clearing House PPM School of Management, 2011)
At first, the history of the establishment of Islamic banks is intended as an alternative to conventional interest-based bank. The Islamic banking industry proved its strength to face the economic crisis. Islamic banking is also noted to have a much better growth compared with conventional banking. However, the growth of Bank Danamon – Sharia Business Unit (UUS), founded in 2002, looks not meet expectations. This condition leads to the preliminary studies and research to find the best form of sharia Bank Danamon, in order to achieve the growth targets set by the Management. To get the best form of sharia, conducted by collecting and organizing important information you need, evaluate the results (outcomes) of any decisions taken, and plan on projecting the expected results. At least there are three informations or elements necessary to produce a quality decision, namely: the existence of clear objectives (goals), alternatives or options that can be run (alternative), and the factors that influence the decision making (criterion). BOCR analysis is then used to find the best way of solving problems by considering the various criteria that give significant influence on an issue. The analysis was performed by using the method of AHP/ANP that gave rise to three scenarios for the results (outcomes) that you expect: standard conditions (B/C); pessimistic B/(CxR); and realistic conditions (BxO)/(CxR) . The best alternative is selected that has the highest value use scenarios realistic condition. With BOCR analysis using three scenarios, i.e.: standard scenario, pessimistic, and realistic, founded that SPIN-OFF option remains the best option.